Preparative SDS PAGE as an Alternative to His-Tag Purification of Recombinant Amelogenin - Gabe, Claire M.; Brookes, Steven J.; Kirkham, Jennifer (Frontiers in Physiology, 2017)
Recombinant protein technology provides an invaluable source of proteins for use in structure-function studies, as immunogens and in the development of therapeutics. Recombinant proteins are typically engineered with “tags” that allow the protein to be purified from crude host cell extracts using affinity based chromatography techniques. Amelogenin is the principal component of the developing enamel matrix and a frequent focus for biomineralisation researchers. Several groups have reported the successful production of recombinant amelogenins but the production of recombinant amelogenin free of any tags, and at single band purity on silver stained SDS PAGE is technically challenging. This is important, as rigorous structure-function research frequently demands a high degree of protein purity and fidelity of protein sequence. Our aim was to generate His-tagged recombinant amelogenin at single band purity on silver stained SDS PAGE for use in functionality studies after His-tag cleavage. An acetic acid extraction technique (previously reported to produce recombinant amelogenin at 95% purity directly from E. coli) followed by repeated rounds of nickel column affinity chromatography, failed to generate recombinant amelogenin at single band purity. This was because following an initial round of nickel column affinity chromatography, subsequent cleavage of the His-tag was not 100% efficient. A second round of nickel column affinity chromatography, used in attempts to separate the cleaved His-tag free recombinant from uncleaved His-tagged contaminants, was still unsatisfactory as cleaved recombinant amelogenin exhibited significant affinity for the nickel column. To solve this problem, we used preparative SDS PAGE to successfully purify cleaved recombinant amelogenins to single band purity on silver stained SDS PAGE. The resolving power of preparative SDS PAGE was such that His-tag based purification of recombinant amelogenin becomes redundant. We suggest that acetic acid extraction of recombinant amelogenin and subsequent purification using preparative SDS PAGE provides a simple route to highly purified His-tag free amelogenin for use in structure-function experiments and beyond.